Analisis Rasio Profitabilitas dan Aktivitas - Aini, Nur; Hasanuddin, Hasanuddin; Machmud, Mulyana (Fakultas Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2022)
This study aims to find out the increase in profitability and activity at PT. Hendra Mandiri Parepare Services. The research results collected are processed and analyzed in this section. The analysis used in this study includes descriptive analysis and hypothesis testing. The analytical method used in this research is quantitative and qualitative data. By using the method of profitability and activity ratio analysis. The object of the research is to use financial statements in the form of a balance sheet and profit and loss. For the profitability ratio from the calculation of gross profit margin (GPM) at PT. Hendra Mandiri Parepare's services for 2019, 2020, and 2021 are 35% each; 30%; and 26%. The gross profit margin in 2016 and 2017 is considered very good. Then the results of the calculation of the net profit margin (NPM) at PT. Hendra Mandiri Parepare services for 2019, 2020, and 2021 are 15% each; 16%; and 6%. Net profit margin in 2019 and 2020 is considered Good. And the results of the calculation of return on investment (ROI) at PT. Hendra Mandiri Parepare's services for 2019, 2020, and 2021 are 21% each; 28%; and 10%. Return on investment in 2016 and 2017 is considered good. 4) For the activity ratio of the calculation of receivable turnover at PT. Hendra Mandiri Parepare services for 2019, 2020, and 2021 for 4 times each; 6 times; and 7 times. receivable turnover for three years is considered very poor every year. Then the results of the calculation of total asset turnover at PT. Hendra Mandiri Parepare services for 2019, 2020, and 2021 for 1 time each; 2 times, and 2 times. total asset turnover in 2019 is categorized as poor.